2015
DOI: 10.5014/ajot.2015.69s1-rp103a
|View full text |Cite
|
Sign up to set email alerts
|

Effectiveness of a Behavioral Intervention to Help Individuals Manage Posttraumatic Brain Injury Fatigue

Abstract: Date Presented 4/16/2015 A significant proportion of individuals with traumatic brain injury (TBI) experience persistent and significant fatigue that affects their daily life. The Maximizing Energy (MAX) intervention is a promising behavioral intervention that has been shown to decrease the impact of post-TBI fatigue on everyday life.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 0 publications
0
2
0
Order By: Relevance
“…Studies exploring fatigue-specific education groups did not demonstrate any statistical significant results on formal fatigue measures; however, qualitative results revealed improvements in understanding fatigue patterns (Humphries 2017) and implementing fatigue management strategies (Cooper et al 2009;Killington et al 2021). Formalised interventions, such as the MAX intervention, demonstrated varied results, with one RCT demonstrating significant improvements for fatigue over time (Whyte et al 2015) whereas another with similar study size and methodology only recorded small-medium effect sizes (Raina et al 2016). A subsequent paper (Raina et al 2022) applying more sophisticated analysis techniques demonstrated significant differences for the MAX group at post-intervention and 8 week follow up.…”
Section: Psychological Interventionsmentioning
confidence: 99%
See 1 more Smart Citation
“…Studies exploring fatigue-specific education groups did not demonstrate any statistical significant results on formal fatigue measures; however, qualitative results revealed improvements in understanding fatigue patterns (Humphries 2017) and implementing fatigue management strategies (Cooper et al 2009;Killington et al 2021). Formalised interventions, such as the MAX intervention, demonstrated varied results, with one RCT demonstrating significant improvements for fatigue over time (Whyte et al 2015) whereas another with similar study size and methodology only recorded small-medium effect sizes (Raina et al 2016). A subsequent paper (Raina et al 2022) applying more sophisticated analysis techniques demonstrated significant differences for the MAX group at post-intervention and 8 week follow up.…”
Section: Psychological Interventionsmentioning
confidence: 99%
“…Physical and mental fatigue was the focus of multifaceted psychosocial education groups described in eight articles, implementing sessions on health education, symptom control and behavioural change(Cooper et al 2009; Howe et al 2019;Stubberud et al 2019;Audrit et al 2021;Killington et al 2021). The Maximising Energy (MAX) intervention also utilised in problem-solving therapy for managing fatiguerelated problems(Whyte et al 2015;Raina et al 2016Raina et al , 2022. Activity-based interventions were described in five articles.…”
mentioning
confidence: 99%